Unlocking the Power of Canva: Students’ Views on Using the All-In-One Tool for Creativity and Collaboration - John Erwin Pedroso; RV S. SULLEZA; Keith Hae Moon C. FRANCISCO; Ayya Jade O. NOMAN; Chynna Althea V. MARTINEZ (RADINKA JAYA UTAMA PUBLISHER, 2023)
As technology continues to be integrated into the field of education, many students and teachers turn to digital tools to enhance their learning and teaching experience. Among these tools is Canva, a web-based graphic design platform. This qualitative descriptive study seeks to investigate the views of students on using Canva as an all-in-one tool for creativity and collaboration. It was conducted among eight (8) Bachelor of Secondary Education (BSED) major in Social Studies students who were identified through a purposeful sampling technique. The students were asked to write narratively in a written interview questionnaire based on Graham Gibbs' reflective cycle that was created using Google Docs. The analysis revealed three (3) main themes: unique features (user-friendliness, diverse applications, and efficient collaboration), positive effects on creativity and collaboration (continued usage, enhanced skills, and increased satisfaction), and drawbacks (application’s limitations and users’ limitations). The results demonstrated that students have predominantly positive opinions of Canva. It enables them to unleash their creativity, optimize collaboration, and produce visually captivating designs. However, they also acknowledged that despite its user-friendliness and comprehensive features, Canva has certain disadvantages that may come from the application and the students themselves. Factors like overreliance on the application and weak connectivity may pose a challenge to their design process. Nevertheless, Canva remains a valuable digital tool for students in enhancing their educational endeavors.